PENERAPAN CORPORATE UNIVERSITY DI BPSDM PROVINSI JAWA TIMUR DALAM MENDORONG PENINGKATAN KINERJA ORGANISASI PERANGKAT DAERAH JAWA TIMUR - AKA, BIASWORO ADISUYANTO; DARTO, MARIMAN; TRIONO, ANANG (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2024)
This research aims to explore the implementation of Corporate University in the Human Resources Development Agency (BPSDM) of East Java Province and its impact on improving the performance of regional apparatus organizations in the East Java region. The research method used is qualitative with a case study approach. Data was collected through in-depth interviews with key stakeholders, participatory observation, and analysis of documents related to the implementation of Corporate University. The research results show that the implementation of Corporate University in BPSDM East Java Province has made a positive contribution to improving the performance of regional apparatus organizations. These findings were obtained through identifying the success of training programs, increasing employee competency, and the effectiveness of the learning methods applied. The implications of these findings for increasing the capability and efficiency of regional apparatus organizations in East Java Province are also discussed in depth. This research confirms that the Corporate University can be an effective instrument in encouraging increased performance of public sector organizations. Discussion of the interaction between the Corporate University and regional organizations is the main focus in analyzing the positive impacts produced. Suggestions are given to further optimize certain aspects in the implementation of Corporate University to ensure sustainability and continuous improvement in the context of human resource development in similar organizations. ABSTRAKPenelitian ini bertujuan untuk mendalami penerapan Corporate University di Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jawa Timur dan dampaknya terhadap peningkatan kinerja organisasi perangkat daerah di wilayah Jawa Timur. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan studi kasus. Data dikumpulkan melalui wawancara mendalam dengan pemangku kepentingan utama, observasi partisipatif, dan analisis dokumen terkait implementasi Corporate University. Hasil penelitian menunjukkan bahwa penerapan Corporate University di BPSDM Provinsi Jawa Timur telah memberikan kontribusi positif terhadap peningkatan kinerja organisasi perangkat daerah. Temuan ini diperoleh melalui identifikasi keberhasilan program pelatihan, peningkatan kompetensi pegawai, dan efektivitas metode pembelajaran yang diterapkan. Implikasi temuan ini terhadap peningkatan kapabilitas dan efisiensi organisasi perangkat daerah di Provinsi Jawa Timur juga dibahas secara mendalam. Penelitian ini menegaskan bahwa Corporate University dapat menjadi instrumen efektif dalam mendorong peningkatan kinerja organisasi sektor publik. Pembahasan mengenai interaksi antara Corporate University dengan organisasi perangkat daerah menjadi fokus utama dalam menganalisis dampak positif yang dihasilkan. Saran diberikan untuk lebih mengoptimalkan aspek-aspek tertentu dalam implementasi Corporate University guna memastikan keberlanjutan dan perbaikan berkelanjutan dalam konteks pengembangan sumber daya manusia di organisasi sejenis.